PEMBELAJARAN SAINS DAN KARAKTERISTIK SISWA SEKOLAH DASAR KOTA BANJARMASIN - Sholahuddin, Arif; Arsyad, St. Wahidah (Vidya Karya Jurnal Kependidikan, 2014)
This study is a first stage of the research and development of the learning tools of problem based learning model. This study used a survey method to obtain data abaout implementation of learning science in elementary school, and student characteristics comprising cognitive styles and reasoning ability. Furthermore, the datas were analyzed descriptively as the basis of developing the learning tools. Tis study showed that: (1) learning science has been widely implemented the conventional approach and emphasized to the cognitif learning outcomes: âteacher explains the concepts, give exercise to the students, then test the studentsâ understanding, (2) teacher conducted investigation-based learning activities in learning occasionally and students are not familiar to discussion activities and communicate the results of their investigation, (3) science learning have not been considered differences of the studentsâ characteristics (4) students of elementary school with category C and B generally have a field-dependent cognitive style (FD), while students at school with A category distributed in all cognitive style (field dependent, field-intermediate and field- independent/FI), although the most of them with FD cognitive style and (5) majority of elementary students have the concrete reasoning abilities. Based on the above facts, science learning strategy should facilitate students to construct their knowledge meaningfully, train a variety of skills such as social skills, psychomotoric skills, and process skills as well as consider characteristics of the students, so that they they can learn optimally .